Facile Synthesis of Nanosized Magnesium-Aluminium Layered Double Hydroxides - Dhakal, Kedar Nath; Aryal, Girja Mani; Adhikari, Hari Sharan; Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2021)
We report facile methods of preparing nanosized hydrotalcite-like compounds, the layered double hydroxides (LDH), with ordinary chemistry laboratory settings to educate the young scientists from high schools to undergraduate university level fostering their research interest in preparing these nanomaterials of practical importance. Coprecipitation and urea hydrolysis methods have been recommended as facile routes of preparing the magnesium-aluminum layered double hydroxides (Mg-Al LDHs). The LDH thus prepared were characterized by Fourier transform infrared (FTIR) spectroscopic and powder X-ray diffraction (XRD) techniques. The observed weakening of some FTIR peaks and XRD planes shifting concerning standard JCPDS 89-5434 data implied the slight structural variation of the compounds and the presence of impurities. The average grain diameter of LDH particles was found in the range of 20 to 60 nm.